The Existence of Moral Education in Strengthening the Supremacy of Law in Indonesia in Era Society 5.0 - Anissa; Firman (Konsultan Jurnal Ilmiah Indonesia, 2025)
This study aims to analyze the role and existence of moral education in efforts to strengthen the supremacy of law in Indonesia in the era of society 5.0. Using a descriptive qualitative approach, this study examines how moral education can be a foundation in building public legal awareness amidst digital transformation. Data collection was conducted through literature studies, in-depth interviews with education experts, legal practitioners, and policy makers, as well as observations of the implementation of moral education in various educational institutions. The results of the study indicate that moral education has a strategic role in shaping the character and legal awareness of the Indonesian people. In the era of society 5.0, where human interaction is increasingly integrated with digital technology, moral education faces new challenges in transmitting ethical and moral values. The study identified three main aspects: (1) the urgency of revitalizing moral education in the national education curriculum, (2) the importance of synergy between moral education and law enforcement, and (3) adaptation of moral learning methods that are relevant to the characteristics of the digital era. The research findings indicate that strengthening moral education contributes significantly to increasing public legal awareness, which is reflected in the decreasing rate of legal violations among the younger generation. This study recommends the need to develop an integrative moral education model, involving the active role of families, educational institutions, and communities, and utilizing digital technology as an effective learning medium.